2013
DOI: 10.1063/1.4829905
|View full text |Cite
|
Sign up to set email alerts
|

Favorable electronic structure for organic solar cells induced by strong interaction at interface

Abstract: Articles you may be interested inEffect of co-adsorption dye on the electrode interface (Ru complex/TiO2) of dye-sensitized solar cells AIP Advances 3, 072113 (2013);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The binding energy between the BCP and Ag is 0.15 eV calculated as the difference in the total energy. The predicted molecular structure is consistent with the recent X-ray photoemission study on BCP and Mg complex where a strong bond between the nitrogen atoms of BCP and the metal atom was suggested …”
Section: Resultssupporting
confidence: 89%
“…The binding energy between the BCP and Ag is 0.15 eV calculated as the difference in the total energy. The predicted molecular structure is consistent with the recent X-ray photoemission study on BCP and Mg complex where a strong bond between the nitrogen atoms of BCP and the metal atom was suggested …”
Section: Resultssupporting
confidence: 89%
“…15,16) In our previous work, we have clarified the electronic properties of BCP=metal interface. [17][18][19] We also have demonstrated that BCP can be used as a buffer layer in inverted OSCs. 20) However, the function of BCP in an inverted OSC is still not yet fully understood.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, the origin of the gap states is the Al-BCP complex formation. 14 The unoccupied gap states should act as a transport level from C 60 to the Al cathode since the BCP LUMO is energetically too far to accept electrons. From the well-matched theoretical results with the UPS and IPES measurements, the formation of the Al-BCP complex giving occupied and unoccupied gap states in the original band gap of BCP is confirmed.…”
Section: B Theoretical Studymentioning
confidence: 99%
“…To determine the transport levels of BCP, the electronic structures of the Al/BCP interface have been studied and interfacial gap states have been reported. [14][15][16][17] In addition, Nakayama et al reported another gap state at the BCP/C 60 interface. 18 However, in these studies, only occupied gap states below the Fermi level (E F ) were measured, which are not an associated level for electron transport directly.…”
Section: Introductionmentioning
confidence: 99%